Food supplements and toxic bait used to manage the coffee leaf-miner and its natural enemies in a conventional crop system - Carlos Ecole, Carvalho; Campos Moraes, Jair; Vilela, Michelle (Coffee Science - ISSN 1984-3909)
This work assessed the effect of food supplements on the population of the coffee leaf-miner Leucoptera coffeella (Guérin-Mèneville & Perrottet) (Lepidoptera: Lyonetiidae) and its natural enemies. The experiment was set up at the Federal University of Lavras (UFLA) in a five-year-old dense, conventional cv. Rubi crop planted in a 2.0 x 0.6 m spacing. The experimental design was in randomized blocks with six treatments and four replications. The treatments were: beer yeast and honey (1:1) at 20%, molasses at 10%, hydrolyzed protein at 2%, hydrolyzed protein at 2% with cartap (20 g a.i./ha) (toxic bait), cartap (20 g a.i./ha) and control (water). The features assessed were: percentage of mined leaves, percentage of mined leaves preyed on by wasps, number of live coffee leaf-miner caterpillars, number of pupae formed per sixty leaves and the percentage of parasitism. The most important parasitoids were Orgilus niger, Centistidea striata, Stiropius reticulatus and Horismenus sp. After application of the toxic bait and cartap insecticide treatments, a reduction in both the total parasite population and per parasitoid species was observed. The results suggest further studies for recommending food supplements as a pest management tactic in coffee crops. Toxic bait used to manage the coffee leaf-miner affected negatively the population of its natural enemies.